2014
DOI: 10.3855/jidc.4496
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of mutations in the rpoB gene of multidrug-resistant Mycobacterium tuberculosis clinical isolates from Sudan

Abstract: This item has no abstract, Follow the links below to access the full text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 13 publications
6
10
2
Order By: Relevance
“…15,16 The occurrence of 531 mutations (11.7%) in this study was comparable to 9.4% found in the previous study. 10 Our finding and those of Burkina Faso neighboring countries 11,[12][13][14] contrast enormously with the results of numerous studies [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] which reported higher rates of mutations at 531. High rates of 531 mutations were particularly found in Kyrgyzstan, Ethiopia, Brasil, South West Ethiopia, Georgia, Taiwan and Samara in Russia.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…15,16 The occurrence of 531 mutations (11.7%) in this study was comparable to 9.4% found in the previous study. 10 Our finding and those of Burkina Faso neighboring countries 11,[12][13][14] contrast enormously with the results of numerous studies [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] which reported higher rates of mutations at 531. High rates of 531 mutations were particularly found in Kyrgyzstan, Ethiopia, Brasil, South West Ethiopia, Georgia, Taiwan and Samara in Russia.…”
Section: Discussioncontrasting
confidence: 98%
“…It corroborated with similar reports from elsewhere. 17,36,37 It is possible that less common mutations in rpoB gene cannot be detected by DRplus. 21 In addition, the possibilities of absence of mutation in RRDR of rpoB gene in MDR-TB isolates may be due to existence of other rare rpoB mutations outside RRDR or different mechanism of rifampicin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported vastly variable frequencies of these mutations; with katG315 gene mutations accounting for 42 to 95% and mutation in the inhA-15 promotor region accounting for 6 to 43% of phenotypic INH resistance [12,16,17,22,23]. that the frequency of gene mutation at codon 531, 526 and 516 were 64.1%, 17.9%, and 7.7%, respectively [9]. The same repot revealed that all genetic alterations were occurred by single base substitutions, and the most common mutation was observed at codon S531L [9].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study conducted by Elbir et al . from Sudan reported that the frequency of gene mutation at codon 531, 526 and 516 were 64.1%, 17.9%, and 7.7%, respectively [9]. The same repot revealed that all genetic alterations were occurred by single base substitutions, and the most common mutation was observed at codon S531L [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation